Le langage reflète et façonne les réalités sociales : une prise de position de la RFRE - Nussbaumer, Léa Camille Justine; Pellerin, Marc-André; Mathilde, Berger; Borda Calisaya, Alison; Mottaz, Clarisse; Paupelin, Virgile; Kühne, Nicolas (Revue Francophone de Recherche en Ergothérapie, 2022)
Sans résumé